PENGGUNAAN ZONA NILAI TANAH DI DALAM PENILAIAN HARGA TANAH SEBAGAI DASAR PENETAPAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN DI KABUPATEN SIDOARJO - Muzdalifah Lutfi; Tunggul Anshari SN; Titik Soeryati Soekasi (Jurnal Akuntansi dan Pajak, 2022)
The purpose of this study is to describe and analyze the causes of land value zones as one of the variables of land price assessment to determine BPHTB and analyze and solve practical problems regarding the legal strength and validity of land value zones that are used as the basis for land price assessment. This research uses qualitative analysis, this type of research is a type of empirical research. The results of the study showed that the calculation of BPHTB Dispenda Tax using Market Value, self-assessment, and database collected as a reference in determining the price or value of a land, so that DISPENDA Sidoarjo Regency also makes ZNT as one of the comparison variables in determining the value of land and buildings attached to the land because in determining ZNT is also one of them using market value. In addition, all DISPENDA still imposes its authority to conduct assessments of land and buildings for tax payments because there has been no firm action on the assessment and there have been no regulations affirmed for the implementation of local taxation on BPHTB. Keywords : Land Value Zone, Land Price Assessment, BEA, Land and Building Rights.